Impact of Coolant and Speed on Stainless Steel with Opening Machining Efficiency: Dampak Pendingin dan Kecepatan pada Baja Tahan Karat dengan Membuka Efisiensi Pemesinan - Alifiana , Yesi; Fahruddin, A’rasy (Indonesian Journal of Innovation Studies, 2024)
This study investigates the impact of coolant types (water coolant, cutting oil, and air blow) and rotational speeds on machining outcomes for stainless steel SUS 304 using insert tools on CNC lathe machines. Conducted at PT. WIDJAYA TEKNIK ENGINEERING, a manufacturing company, the research employs experimental methods alongside literature review and field observations. Results reveal significant effects of rotational speed on coolant efficacy, influencing production metrics such as dimensional accuracy, machining time, and surface finish quality. Notably, cutting oil demonstrates superior performance over air blow coolant at specific speeds. These findings provide valuable insights for optimizing coolant selection and machining parameters, thereby enhancing production efficiency and product quality in machining processes. Highlights: Experimental Study: Investigating coolant types and rotational speed on machining outcomes. Optimizing Production: Enhancing efficiency and quality through coolant and speed optimization. Industry Insights: Applicable findings for machining stainless steel on CNC lathe machines. Keywords: Coolant types, Rotational speed, Machining outcomes, CNC lathe machines, Stainless steel SUS 304.